The potential of machine learning in computer aided geometric design / Siti Sarah Raseli and Assoc. Prof. Dr Ahmad Lutfi Amri Ramli - Raseli, Siti Sarah; Ramli, Ahmad Lutfi Amri (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Artificial Intelligence (AI) is a leading technology that is capable of simulating human intelligence and decision making (Song et al., 2022). Artificial intelligence is an advanced technology that is widely applied in various fields such as mathematics, statistics, and computer science across a wide range of industries. Machine learning is a part of AI that enables the extraction of information from data to improve its ability by studying from experience (Bertolini et.al, 2021). Machine learning is the development of computational algorithms that aim to imitate human intelligence through environmental education (El Naqa & Murphy, 2015). Machine learning is a generally accepted application that can be applied in various studies. The techniques proposed from machine learning are widely used to solve problems that arise in many fields and industries. In addition, machine learning applications can improve efficiency, accuracy and increase performance and productivity.